PENGARUH ETIKA KERJA ISLAM DAN BIG FIVE PERSONALITY TERHADAP ORGANIZATION CITIZENSHIP BEHAVIOR (OCB) - Indah Rohyani; Siti Nur Azizah (Jurnal Inovasi Penelitian, 2023)
This study aims to examine the effect of Islamic work ethics and big five personality variables on Organizational Citizenship Behavior (OCB) in Medical Employees at PKU Muhammadiyah Gombong General Hospital. This research is descriptive quantitative type with purposive sampling method, namely permanent nurses as many as 71 nurses in inpatient wards. Data testing includes validity and reliability tests, classical assumptions, partial tests and simultaneous tests with the help of SPSS 25. The results show that the big five personality on the conscientiousness dimension on the big five personalities in the form of persistence and motivation to achieve goals has the most influence on behavior OCB. Islamic work ethics partially show influence on OCB behavior. Together the big five personalities and Islamic work ethics influence OCB behavior in permanent nurses at PKU Muhammadiyah Gombong Hospital.